Pengaruh Bauran Promosi Terhadap Keputusan Nasabah Dalam Memilih Produk Pembiayaan - Lilis Muhlisoh; Kholil Nawawi; Suyud Arif (Prodi Perbankan Syariah FAI UMT, 2020)
The purpose of this study was to determine the promotional strategy undertaken by SRB HIK Insan Cita and its influence on the customer's decision in choosing financing. This research uses quantitative methods that are descriptive in nature. Data sources used are primary and secondary data. The population used was 300 customers and solvin formula used to be 67 sample respondents. Data collection techniques used by researchers are using respondents (questionnaires) and interviews. The method of data analysis in this study uses simple linear regression analysis. Promotional mix variables consisting of advertising (advertising), personal selling (personal selling), sales promotion (seles promotion), publicity (publicity) by conducting a t test shows each variable has a significant influence on the purchase decision variable. Judging from the significant advertising variable 0.038, personal selling 0.001, selles promotion 0.039, and publicity 0.002, which means it is smaller than the significant level used that is 0.05. And can also be seen by t count of 2,126, 3,366, 2,108, 3,248 which means t count 0,224. From the results of the analysis examined that the promotion mix strategy significantly influences customer decisions.